ANALISIS PERUBAHAN GARIS PANTAI PADA BAGIAN HILIR DAS LIMAU KABUPATEN PADANG PARIAMAN - ronal wilnika; Widya Prarikeslan (DEPARTEMEN GEOGRAFI FIS UNP, 2022)
This study aims to analyze changes in coastline, land cover and sedimentation in the cathment are Limau. The methods used in analyzing the data are digitizing satellite images, interpreting satellite images, and Total Suspended Solid in the cathment area Limau. The results show that the largest land use changes occurred in the middle and downstream cathment area Limau, the land changes that occurred were residential land which changed by 29 ha, fields 11 ha, open land 12 ha, rice fields 3 ha, and plantations decreased by 52 ha in 1998 Until 2018, changes in cover affected shoreline conditions in the form of accretion and coastal abrasion which were influenced by sedimentation in the cathment area Limau which changed. Abrasion of 1.59 ha and accretion of 4.8 ha in 1998-2003 and accretion of 20.37 ha in 2003- 2018. The greatest sedimentation occurred around the mouth of the Das Limau river, the largest sedimentation occurred in 2018 while for the previous year the sedimentation rate was not too large.